Low-frequency instabilities due to energetic oxygen ions - Singh, S.V.; Kakad, Amar; Reddy, R.V.; Lakhina, G.S. (My University, 2004)
Low-frequency instabilities excited by energetic oxygen ions are investigated. The model consists of Maxwellian distributions for electrons and protons and Dory–Guest–Harris loss-cone distribution for oxygen ions. The electrons and protons are treated as magnetized and oxygen ions as unmagnetized. The response of the electrons is fully electromagnetic and that of the protons and oxygen ions is electrostatic. A possible application of the investigation to space plasmas is pointed out.
Keywords: Space plasmas; Energetic oxygen ions; Electromagnetic